Intraoperative Three-Dimensional Imaging in Selective Decompression for Lumbar Spinal Stenosis: A Useful Tool in Theory but Also in Everyday Practice? - Uwe Max Mauer; Ulrich Kunz; Chris Schulz (Radiology Research and Practice)
Background. We conducted a pilot study to investigate the value of an Iso-C3D imaging system in determining the extent of decompression of lumbar spinal stenosis during surgery. We now address the question whether this imaging has become a routine tool. Material and Methods. Ten patients who underwent unilateral decompression for lumbar spinal stenosis were intraoperatively examined using the Iso-C3D imaging system. Four years after this study, we investigated whether this intraoperative imaging modality is still being used. Results. Evaluable images were intraoperatively obtained for all patients. In two cases, the surgical procedure was changed on the basis of the images. Myelography did not provide any additional information. In the four years following the study, this intraoperative imaging technique has not been used again. Conclusion. Intraoperative imaging using the Iso-C3D system provides additional safety. It, however, has not become established as a routine procedure.